Global Peace Summit in the International Coordinate System - Kyrydon, Alla; Troyan, Serhiy (Mediaforum : Analytics, Forecasts, Information Management, 2024)
The main attention is focused on an important event of recent months - the Global Peace Summit. This international meeting of leaders of countries and governments took place on June 15-16, 2024 in the Swiss mountain hotel Bürgenstock. It is emphasized that Russia’s war against Ukraine has caused the current transformation of the entire system of modern international relations, which prompts the formation and development of a new architecture of international relations and actualizes relevant studies of these complex and ambiguous processes. The unjustified aggression of the Russian Federation against Ukraine and the aggressor state’s violation of the fundamental principles of international law significantly transformed the understanding of threats to peace and security. Since the beginning of the Russian-Ukrainian war, the problem of guaranteeing security in global and regional dimensions has been present among the key goals of the foreign policy of the global security structure. This prompted the states to strengthen cooperation within existing associations and create new forms of cooperation to counter the Russian Federation. In the conditions of high probability of protracted nature of the war of the Russian Federation against Ukraine and the absence of ready-made solutions to stop the aggression against Ukraine and prevent its escalation, it is urgent to use various platforms to find answers to the difficult challenges of the time. The Global Peace Summit became one of these platforms. The article highlights the prerequisites of the forum, specifies the purpose, goals and objectives of the inaugural Global Peace Summit. The composition of the participants was considered. Attention is focused on the nature of the adopted document and the importance of the forum.